1990
DOI: 10.1103/physrevlett.65.309
|View full text |Cite
|
Sign up to set email alerts
|

Observation of high-lying resonances in theHion

Abstract: Several series of doubly excited resonances have been observed in H ~ photodetachment, appearing as dips in the production cross section of excited neutral hydrogen. At least three resonances are clearly visible converging on each of the thresholds /! ™5, 6, 7, and 8. The data support recent theoretical calculations for the energies of doubly excited resonances and verify a Rydberg-dipole formula for the main resonance positions.PACS numbers: 32.80.FbThe dipole potential of an excited hydrogen atom polarized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(16 citation statements)
references
References 11 publications
(2 reference statements)
0
16
0
Order By: Relevance
“…Keeping only the lowest "+" states converging to each threshold H(n), they were able to interpret the doubly excited resonance structures converging to the n = 4-8 thresholds that were observed in the photodetachment measurements of Harris et al [14] Sadeghpour and Greene [19] interpreted these observed resonances as the doubly excited states supported by the lowest "+" adiabatic hyperspherical radial potentials, as shown in Figure 1.…”
Section: Doubly Excited State Spectra Of H -And Hementioning
confidence: 92%
See 3 more Smart Citations
“…Keeping only the lowest "+" states converging to each threshold H(n), they were able to interpret the doubly excited resonance structures converging to the n = 4-8 thresholds that were observed in the photodetachment measurements of Harris et al [14] Sadeghpour and Greene [19] interpreted these observed resonances as the doubly excited states supported by the lowest "+" adiabatic hyperspherical radial potentials, as shown in Figure 1.…”
Section: Doubly Excited State Spectra Of H -And Hementioning
confidence: 92%
“…Clearly, however, the simple single-configuration picture presented above gives a qualitative, order-of-magnitude understanding of why the Be + 1s 2 2s ionic state cross section is so small. Namely, the transition matrix element to the 2s state is subject to extensive cancellations, as revealed in (14), whereas the transition matrix elements to the np states are not, as revealed in (13).…”
Section: Resonant Photoionization Of the Be 1smentioning
confidence: 99%
See 2 more Smart Citations
“…The properties of such states are substantially influenced by the effects of electron-electron correlation. A great amount of theoretical and experimental effort has been devoted to the prototype negative ion, H − [1][2][3][4][5][6][7]. Here, two electrons move in the pure Coulomb field of the nucleus; a case resembling the helium atom.…”
Section: Introductionmentioning
confidence: 99%